2015
DOI: 10.1155/2015/492683
|View full text |Cite
|
Sign up to set email alerts
|

Static Magnetic Field Attenuates Lipopolysaccharide‐Induced Inflammation in Pulp Cells by Affecting Cell Membrane Stability

Abstract: One of the causes of dental pulpitis is lipopolysaccharide- (LPS-) induced inflammatory response. Following pulp tissue inflammation, odontoblasts, dental pulp cells (DPCs), and dental pulp stem cells (DPSCs) will activate and repair damaged tissue to maintain homeostasis. However, when LPS infection is too serious, dental repair is impossible and disease may progress to irreversible pulpitis. Therefore, the aim of this study was to examine whether static magnetic field (SMF) can attenuate inflammatory respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…Pseudomonas aeruginosa LPS has a toxic effect on DPSCs in a dose-dependent manner [ 95 ]. Pretreatment with static magnetic field (SMF) attenuates inflammatory response and increases viability of cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pseudomonas aeruginosa LPS has a toxic effect on DPSCs in a dose-dependent manner [ 95 ]. Pretreatment with static magnetic field (SMF) attenuates inflammatory response and increases viability of cells.…”
Section: Resultsmentioning
confidence: 99%
“…Pretreatment with static magnetic field (SMF) attenuates inflammatory response and increases viability of cells. SMF can also enhance the proliferation of DPSCs [ 95 ].…”
Section: Resultsmentioning
confidence: 99%
“…LPS-induced dental pulp inflammation represents a stable experimental inflammation model for the dynamic observation of the progress of acute and chronic pulpitis, as well as other oral inflammatory diseases in rodents [ 27 , 34 ]. Previous studies have shown that LPS-treated inflammation is induced in a time- and dose-dependent manner in dental pulp cells [ 35 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Tooth pulp developing from dental papilla consists of odontoblast, fibroblast, blood, and neural veins [17]. Odontoblast cells are the most important cells of the pulp.…”
Section: Dental Pulpmentioning
confidence: 99%